Microbiological Quality Of Linus Chicken Meat Fed With Moringa Leaf Flour - MUTMAINNA, ANDI; Jamili, Muhammad Arsan; Hidayat, Muhammad Nur; Ananda A, Suci; Ningsih, Sri Wahyu (Jurnal Sains dan Teknologi Pangan, 2022)
Moringa leaf flour is incorporated to commercial feed in order to improve the microbiological quality of chicken meat. The chicken was fed with formulated feeds prepared using different methods (steaming, fermentation, withering) and various doses. Microbiological test included total plate count (TPC), lactic acid bacteria (LAB), pH of meat was also checked. The experiment was arranged using completely randomized design with 4 treatments and 3 replications. The results showed that addition of moringa leaf flour into feed influenced microbiological quality of linus chicken meat.Keywords:  Linus Chicken, Meat, Moringa Leaf Flour , Total Plate Count , lactic acid bacteria, pH